Analisis Faktor-Faktor Penghambat Pembelajaran Membaca Permulaan Siswa Kelas 1 SDN 5 Sembawa - Gisela, Gita; Hermansyah, Hermansyah; Jayanti, Jayanti (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to determine the factors that inhibit students' learning of beginning reading in grade I SD Negeri 5 Sembawa. This research uses descriptive qualitative research methods. Data collection techniques used by researchers are teacher interview observations, student interviews, student-parent questionnaires, and documentation. Data analysis techniques use data reduction, data presentation, and conclusion drawing. The results showed that the factors inhibiting reading learning in grade I students ofSD Negeri 5 Sembawa were internal factors (within students) and external factors (outside students). Internal factors include lack of motivation to read, students' weak memory making it difficult to recognize letters, lack of interest in reading, absence of students' attention while learning, smaller age than their peers, and students do not attend kindergarten (TK). External factors include parents' lack of motivation for their children, lack of interaction between parents and students, lack of parental guidance, parents'lack of learning facilities at home, and unfavorable environmental conditions. The results of this studycan be used to improve the quality of learning to read beginning grade I students who can develop an interest in reading for low-grade students.